2012
DOI: 10.1080/19475721.2012.670666
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes as indicators of environmental quality in seagrass (Posidonia oceanica) meadows of the NW Mediterranean Sea

Abstract: Meiofauna in sediments colonized by Posidonia oceanica in the Ligurian Sea (NW Mediterranean) was investigated to evaluate its use as an early warning indicator of environmental disturbance. Descriptors commonly used in seagrass health assessment are mainly related to the plant (e.g., phenological parameters) and/or to the meadow (e.g., structural parameters) and are subjected to long-term response times. Conversely, meiofauna is considered a good bioindicator with a rapid response to environmental variations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
1
10
1
Order By: Relevance
“…This is in contrast with most studies on meiofauna in seagrass meadows sediments (e.g. Fonseca et al, 2011;Losi et al, 2012) where nematodes dominate numerically. Nevertheless, dominance of copepods is often documented for seagrass meadow canopy leaves (Hall & Bell, 1993;De Troch et al, 2001;Hooper & Davenport, 2006).…”
Section: Discussioncontrasting
confidence: 77%
“…This is in contrast with most studies on meiofauna in seagrass meadows sediments (e.g. Fonseca et al, 2011;Losi et al, 2012) where nematodes dominate numerically. Nevertheless, dominance of copepods is often documented for seagrass meadow canopy leaves (Hall & Bell, 1993;De Troch et al, 2001;Hooper & Davenport, 2006).…”
Section: Discussioncontrasting
confidence: 77%
“…Most sediments of the study area are coarse sands rich in vegetal detritus from seaweeds and P. oceanica. Copepods become typically more abundant with the increase in grain size (Losi et al, 2012; and are often associated with algal or seagrass detritus (Ceccherelli and Mistri, 1990;Mascart et al, 2013Mascart et al, , 2015. As reported in the cited literature, the presence of macrophytal detritus may play an important role as a refuge and food source for these animals, increasing their abundance and diversity (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…At the same time, densely aggregated leaves foster many epiphytes, offering new and more abundant food sources to the meiofauna (Velimirov & Walenta-Simon, 1993;Mascart et al, 2018; but see Lebreton et al, 2012 on Zostera noltii). Indeed, all studies addressing temporal variation in P. oceanica found substantial differences over time, not only in taxa composition and abundance (Novak, 1989;Villora-Moreno et al, 1991;Losi et al, 2012;Cvitković et al, 2017;Polese et al, 2018), but also in species' dietary preferences (Mascart et al, 2018). These studies collectively showed that abundances of most meiofaunal taxa peaked between spring and summer (Novak, 1982(Novak, , 1989Villora-Moreno et al 1991;Sánchez-Jerez et al 1999a;Losi et al, 2012;Cvitković et al, 2017;Polese et al, 2018), in accordance with the apogee of P. oceanica.…”
Section: Habitat Preferences In P Oceanicamentioning
confidence: 85%
“…Such sheltering effect is stronger in the matte, which also shows a higher diversity than that in the leaves, both in meiofaunal (Novak, 1982(Novak, , 1989Guilini et al, 2017; see Figure 2A and 2D) and macrofaunal species (Gambi et al, 1995;Borg et al 2006;Piazzi et al 2016). Food availability within each habitat, finally, drives the presence of different species not only depending on the amount of food (Mirto et al, 2010(Mirto et al, , 2014Castejón Silvo, 2011;Losi et al, 2012;Mascart et al, 2013;Cvitković et al, 2017;Polese et al, 2018) but also upon the presence of specific food sources. In fact, it has been shown that even closely related meiofaunal species may prefer different food sources (Mascart et al, 2018).…”
Section: Habitat Preferences In P Oceanicamentioning
confidence: 98%